Exploration of Intercultural Attitudes in Collaborative Reflective Writing in an Intercultural Communication Course by English Majors in China - Zhou, Ya; Zhou, Liting (Journal of Educational Research and Policies, 2025)
Intercultural competence (IC) is a key competence for EFL learners and its development is a central goal of the Intercultural Communication courses In China. Within that goal, scholars emphasize the attitudinal dimension—beyond knowledge, skills, and language—especially in predominantly monocultural Chinese classrooms. Against this backdrop, this research conducted a content analysis of 37 collaborative reflective writing based on given videos by English majors from a university in western China, aiming at exploring students’ intercultural attitudes and their relationship between video themes. This research finds that most students hold favorable attitudes — openness, respect and curiosity — towards foreign cultures, while a small number of them show strong evidence of self-awareness and national identity. It also finds that intercultural attitudes are more likely to emerge when students write on familiar preferred video themes — such as university life and language learning. However, videos that address broader and more abstract themes often encourage critical cultural awareness. These findings will not only guide the continued refinement of the course, but also serve as a practical reference to EFL curricula.